GOOD UNIVERSITY GOVERNANCE, REPUTATION RISK, AND PUBLIC ACCOUNTABILITY PRIVATE UNIVERSITIES (PTS) - David, Jenner; Tewal, Bernhard; Sendow, Greis Mike; Trang, Irvan; Lumintang, Genita Gracia (Jurnal Ilmiah Manajemen & Bisnis, 2022)
The purpose of this study was to determine the effect of good university governance and reputation risk management on the public accountability of private universities, especially Halmahera University. The two things above, namely the practice of good university governance and reputation risk management are two interrelated things and must be accounted for to gain trust and strengthen legitimacy from the public as a private university of high quality, highly competitive, and have an impact on the progress of society. This study used a quantitative approach, the data were analyzed using the SPSS version 26 program on 98 samples of permanent lecturers at Halmahera University through a questionnaire that had passed the validity and reliability test. The data analysis aimed to examine the effect of good university governance and reputation risk on public accountability, and good university governance against reputational risk by path analysis method. The results show that Good University Governance has a significant negative effect on Public Accountability, Reputation Risk has a significant positive effect on Public Accountability, and Good University Governance has a significant positive effect on Reputation Risk. Based on the results of this study, it was concluded that the practice of Good University Governance and handling the risk of higher education reputations, especially at the University of Halmahera, would have a good impact on public accountability to provide a better image for the University of Halmahera